Neighborhood Effects and Regional Poverty Traps in Rural China. (16th January 2014) - Fang, Yingfeng; Zou, Wei
Abstract: The present paper investigates how neighborhood effects are connected to chronic poverty. We examine a large sample of groups of households and find that neighborhood effects are significant in a majority of groups, especially in the poorest groups. People living in poor communities tend to suffer from poverty over time. It is of theoretical and empirical importance to explore how neighborhood effects are interrelated with chronic poverty and the channels through which this occurs. Unlike other econometric analyses, we establish a multilevel econometric model to show that: (i) it is difficult for an individual living in a neighborhood with a high proportion of agricultural labor, low education levels, and poor transport and telecommunication infrastructure to escape from poverty traps; (ii) neighborhood effects dominate in poor communities; and (iii) although poverty is affected by group‐level factors, individual factors still play a dominant role in regards to escaping poverty when income surpasses a threshold level. Therefore, policy priority should be given to providing social protection and public services, especially in poor rural areas.